INVESTIGATING THE TYPES OF CODE SWITCHING IN LANGUAGE TEACHING INSTRUCTION IN EFL CLASS OF SMA I NEGERI SAMARINDA - Rusmawaty, Desy (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2018)
Not only as a language interference, code switching was able to be used as one of language teaching strategy. This study investigated the types of code switching used by a teacher in language teaching instruction in EFL class of SMA I Negeri Samarinda. As a case study, an English teacher and third grade students of SMA I Negeri Samarinda were the subjects of this study. The data in the form of utterances between a teacher and her students were collected by taping and recording the natural interaction using video cameras and a voice recording. After transcribed and analyzed the data, this study revealed that a teacher practiced five types of code switching in her language teaching practices, they are (1) inter-sentential code switching, which involves a word within a sentence, a verb phrase, a question tag, and an adverb phrase; (2) inter-sentential code switching; (3) emblematic code switching; (4) intra-lexical code switching; and (5) changing pronunciation features. This study found also as new kind of intra sentential which involves an adverb phrase.